2000
DOI: 10.1109/8.841907
|View full text |Cite
|
Sign up to set email alerts
|

Coupling through tortuous path narrow slot apertures into complex cavities

Abstract: A hybrid finite-element method/method of moments (FEM/MOM) model has been implemented to compute the coupling of fields into a cavity through narrow slot apertures having depth. The model utilizes the slot model of Warne and Chen [24]-[30], which takes into account the depth of the slot, wall losses, and dielectrics with air gaps in the slot region. The cavity interior is modeled with the mixed-order covariant-projection elements of Crowley [33]. Results are given showing the accuracy and generality of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…At present, there are many literatures on aperture coupling with metal cavity (Jedlicka, 2000; SIAH Eng Swee, 2003; Li Kai, 2013;Peng Qiang, 2013) and computer box is the common simulation object, while the optical drive and floppy disk drive are usually considered as complete cavity without holes (Chen Xiuqiao, 2004;Yao Jianming, 2005). This approach is not consistent with the reality.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many literatures on aperture coupling with metal cavity (Jedlicka, 2000; SIAH Eng Swee, 2003; Li Kai, 2013;Peng Qiang, 2013) and computer box is the common simulation object, while the optical drive and floppy disk drive are usually considered as complete cavity without holes (Chen Xiuqiao, 2004;Yao Jianming, 2005). This approach is not consistent with the reality.…”
Section: Introductionmentioning
confidence: 99%
“…In Azaro et al (2002), a circuit approach was proposed for electromagnetic field coupling through rectangular apertures backed by rectangular boxes. To address more complex structures, a hybrid method of moments (MoM)/finite element method (FEM) technique in Jedlicka et al (2000) and Castillo (2001, 2002) was implemented to determine electromagnetic coupling into cavities having thin wires, dielectric materials, and a metal block. In Yang and Volakis (2005) and Siah et al (2003), it was observed that even a single wire could significantly degrade shielding effectiveness at frequencies where the wire becomes resonant.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the original hybrid algorithm was the PhD dissertation of Rüssel Jedlicka [8], [9]. The slot model of Warne and Chen [1] - [7] is used to model the narrow slot aperture.…”
Section: Coupling Into Cavities Containing Wires With Arbitrary Orienmentioning
confidence: 99%